The Role of the Preparatory Hearing of the First Hungarian Code of Civil Procedure - Kristóf Szivós (Journal on European History of Law, 2024)
The first Hungarian code of civil procedure (Act I of 1911) introduced a new structure in civil litigation. The first instance proceeding consisted of two types of hearing: the preparatory hearing and the main hearing. The study examines the role of the preparatory hearing, which had a sole aim, the foundation of the procedure. The main acts of the parties are therefore examined: the presentation of the claim and the defence of the defendant. The possibilities of the defendant are more emphasised since he had more possibilities in the preparatory hearing against the claim of the plaintiff. The topics of the study are examined through fragments from the judicial practice.